2014
DOI: 10.1007/s00284-014-0559-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Melanin in Release of Extracellular Enzymes and Selection of Aggressive Isolates of Bipolaris sorokiniana in Barley

Abstract: Eighteen barley isolates of Bipolaris sorokiniana belonging to wild and clonal type of black, mixed and white subpopulations were quantitatively assayed for their melanin content and aggressiveness with respect to production of some of the extracellular enzymes such as cellulase, pectinase, amylase and protease. Cellulase and pectinase constituted major portion of the enzymes recovered from the black, mixed and white isolates. Enzyme production and aggressiveness were relatively higher in melanin devoid or low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…In the same way, the process of melanization in phytopathogenic fungi directly affects the secretion of proteins, including lytic enzymes (Henson et al, 1999). For instance, the spot blotch caused by the fungus Bipolaris sorokiniana is one of the most important diseases of wheat and barley in South Asia and, recently, a positive correlation was found between high melanin production, elevated amounts of extracellular enzymes, including peptidase, and the aggressiveness of isolates from naturally infected barley (Chand et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…In the same way, the process of melanization in phytopathogenic fungi directly affects the secretion of proteins, including lytic enzymes (Henson et al, 1999). For instance, the spot blotch caused by the fungus Bipolaris sorokiniana is one of the most important diseases of wheat and barley in South Asia and, recently, a positive correlation was found between high melanin production, elevated amounts of extracellular enzymes, including peptidase, and the aggressiveness of isolates from naturally infected barley (Chand et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that TCZ is associated with the absence of melanin production in the cell wall of Bipolaris sorokiniana , as well as a reduction in the production (and size) of spores (Chand et al . ). Application of TCZ reduces the virulence of pathogenic fungi B. sorokiniana (Kunova et al .…”
Section: Introductionmentioning
confidence: 97%
“…It was observed that the more aggressive isolates were able to produce more metabolites. For example, Chand et al (2014) previously reported that extracellular enzymes differed in wild and clonal type populations of Bipolaris sorokiniana. The cellulase production was significantly higher in wild type (11.9 U mg -1 protein) than clonal type (8.15 U mg -1 protein).…”
Section: Resultsmentioning
confidence: 99%